Closed casket : the new Hercule Poirot mystery - Hannah, Sophie, 1971- (Hannah, Sophie, 1971- Hercule Poirot mysteries, 2016)
"What I intend to say to you will come as a shock ..." With these words, Lady Athelinda Playford -- one of the world's most beloved children's authors -- springs a surprise on the lawyer entrusted with her will. As guests arrive for a party at her Irish mansion, Lady Playford has decided to cut off her two children without a penny . . . and leave her vast fortune to someone else: an invalid who has only weeks to live. Among Lady Playford's visitors are two strangers: the famous Belgian detective Hercule Poirot, and Inspector Edward Catchpool of Scotland Yard. Neither knows why he has been invited -- until Poirot begins to wonder if Lady Playford expects a murder. But why does she seem so determined to provoke a killer? And why -- when the crime is committed despite Poirot's best efforts to stop it -- does the identity of the victim make no sense at all?